Rodent Surveys reveal good insights into the Snake Fauna in an Agro-Pastoral Ecosystem in Southern India - Krishnakumar, B.M.; Guptha, Bubesh; Ramanujam, Eric; Ganesh, S.R. (Journal of Biological Studies, 2023)
Rats and mice are among the foremost of agricultural pests that are plentiful in farmlands. Snakes are one of the most specialized natural rat-controlling predatory species, also equally prevalent in farmlands. We studied the snake fauna of agroecosystem in south-eastern India by gathering concomitant data on snakes, during rodent surveys wherein rodents were the main target taxa. From a one year long day-and-night survey focusing on rodents, we obtained 151 sightings of snakes belonging to 22 species (four of which are venomous). A total of 66 sightings representing 14 species were obtained in diurnal surveys, and 21 sightings representing 7 species were obtained in night surveys. As much as 64 sightings representing 20 species were obtained by chance encounters in the study site, but outside of the designated rodent survey duration. An uncommon snake Sibynophis subpunctatus was recorded. The colubrid Ptyas mucosa was the commonest encountered species during the day while at night it was the viper Echis carinatus. Estimated species diversity in Shannon-Wiener index was H = 1.218.